2009
DOI: 10.1007/s00432-009-0566-8
|View full text |Cite
|
Sign up to set email alerts
|

Herbal extract “Songyou Yin” inhibits tumor growth and prolongs survival in nude mice bearing human hepatocellular carcinoma xenograft with high metastatic potential

Abstract: Nontoxic herbal compound extract "Songyou Yin" inhibited tumor growth and prolonged survival, via inducing apoptosis and down-regulation of MMP2 and VEGF, which indicated its potential use in patients with advanced HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…Fufangkushen injection, a patent herbal drug, may inhibit survivin and Bcl2 expression, increase caspase3 expression and induce apoptosis in SMMC7721 cells [131] . Songyou Yin, another patent herbal drug, could induce apoptosis and downregulation of MMP2 and VEGF to inhibit tumor growth and prolong survival [132] (Figure 1). …”
Section: Induction Of Apoptosismentioning
confidence: 99%
“…Fufangkushen injection, a patent herbal drug, may inhibit survivin and Bcl2 expression, increase caspase3 expression and induce apoptosis in SMMC7721 cells [131] . Songyou Yin, another patent herbal drug, could induce apoptosis and downregulation of MMP2 and VEGF to inhibit tumor growth and prolong survival [132] (Figure 1). …”
Section: Induction Of Apoptosismentioning
confidence: 99%
“…Among the members of the TIMP family, particularly TIMP-1 and TIMP-2, can inhibit tumor growth, invasion and metastasis, and also suppress MMP expression (27,30,32). Increased MMP expression, but reduced TIMP expression, were also found in several HCC cell lines with high metastatic potential (21,22,34) including MHCC97H cells. Furthermore, increased TIMP expression reduced invasion and metastasis of cancer cells (5,27), indicating that TIMP exert antimetastatic effects in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the anti-metastatic properties of CIE using the MHCC97H cell line, a typical human HCC cells with high metastatic potential (20,21) that highly expressed MMPs (21,22), and commonly used in the study of antitumor invasion. Furthermore, we determined whether CIE inhibits the migration of MHCC97H cells through a Matrigel-coated membrane, possible modulating the effects of CIE toward the expression of MMPs and TIMPs.…”
Section: Chrysanthemum Indicum Ethanolic Extract Inhibits Invasion Ofmentioning
confidence: 99%
“…It mainly regulates the bioavailability of vascular endothelial growth factor (VEGF), the most potent inducer of tumor angiogenesis and a major therapeutic target (Turpeenniemi-Hujanen, 2005). Some reports demonstrated that herbal extracts have the potential to inhibit the metastatic and angiogenic effects in hepatocellular carcinoma cells by down-regulation of MMP2 and VEGF expression in vitro and in vivo (Huang et al, 2009;Zhang et al, 2009). These studies suggest that TCM could play a vital role in preventing metastasis and anti-angiogenesis in cancers by elucidating the molecular pathways in different cancers that are modulated by TCM.…”
Section: Introductionmentioning
confidence: 99%